2022
DOI: 10.3390/iot3040022
|View full text |Cite
|
Sign up to set email alerts
|

A Holistic Overview of the Internet of Things Ecosystem

Abstract: The Internet of Things (IoT) is a complex ecosystem of connected devices that exchange data over a wired or wireless network and whose final aim is to provide services either to humans or machines. The IoT has seen rapid development over the past decade. The total number of installed connected devices is expected to grow exponentially in the near future, since more and more domains are looking for IoT solutions. As a consequence, an increasing number of developers are approaching IoT technology for the first t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…So far, the Cloud is the prevalent deployment solution adopted for IoT applications, because it offers computing resources on-demand and boundless storage. However, it has been pointed out that connecting IoT devices to the Cloud poses severe issues (Paolone et al, 2022). To fill the gap between IoT devices and the Cloud, the Fog-Edge computing paradigms have been introduced (Ali et al, 2022) The reading of the 55 studies confirmed that ThingsBoard can be used both in Cloud architecture and in Fog/Edge architecture.…”
Section: Main Findingsmentioning
confidence: 99%
“…So far, the Cloud is the prevalent deployment solution adopted for IoT applications, because it offers computing resources on-demand and boundless storage. However, it has been pointed out that connecting IoT devices to the Cloud poses severe issues (Paolone et al, 2022). To fill the gap between IoT devices and the Cloud, the Fog-Edge computing paradigms have been introduced (Ali et al, 2022) The reading of the 55 studies confirmed that ThingsBoard can be used both in Cloud architecture and in Fog/Edge architecture.…”
Section: Main Findingsmentioning
confidence: 99%
“…Additionally, ref. [4] defines IoT platforms in terms of functions and services, i.e., in terms of the characteristics of the IoT infrastructure and the IoT application to be developed; in [5], platforms are classified according to two complementary dimensions: Functional Blocks and Qualities. Finally, ref.…”
Section: Related Workmentioning
confidence: 99%
“…Digital twins are the most complex models that describe the structure, context and behavior of both individual industrial assets and the systems that comprise them (Priyanka E., et al, 2021;Wang P., Luo M., 2021;Fonseca A., et al, 2022;Lehtola V. et al, 2022;Paolone G., et al, 2022;Thürera M., et al, 2022;Valka H. et al, 2022;Zhang R. et al, 2022;Xiang F. et al, 2022). For example, Zambrano V. et al, 2022 in their work "Industrial digitalization in the industry 4.0 era: Classification, reuse and authoring of digital models on Digital Twin platforms" describe the support of the modular design of digital twins through the reuse of their basic building blocks, i.e., the models describing the behavior of the DT, the algorithms associated with them, and the data required for their evaluation.…”
Section: Literature Reviewmentioning
confidence: 99%